The tragedy of Julius Caesar - Shakespeare, William, 1564-1616 (Folger Shakespeare library, 1992)
Presents the annotated text of Shakespeare's tragedy in which Cassius, fearing Julius Caesar's ambition, forms a conspiracy among Roman republicans, including Caesar's trusted friend Brutus, to assassinate him on the Ides of March; and includes scene-by-scene plot summaries, and other reference material.